2017
DOI: 10.1155/2017/8413607
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Life Assessment of Orthotropic Steel Deck with UHPC Pavement

Abstract: In recent years, a number of large-span bridges with orthotropic steel decks were constructed in China. With increasing traffic volumes and higher wheel loads, many fatigue cracks developed at the welds and the edge of cut-out holes. This paper aims at presenting the numerical analysis on the fatigue performance of the orthotropic steel deck using ultrahigh performance concrete (UHPC) overlay as the deck pavement instead of the conventional asphalt concrete pavement. By using finite element method (FEM) model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…As it is clearly visible in Figure 3a, increasing the superplasaticizer decreased the modulus of elasticity that is because of increasing the workability and porosity of concrete [10]. Also, increasing the amount of cement increased the modulus of elasticity of UHPC which is due to increasing of hydration and packing density [11,12]. In Figure 3b, effect of w/c cement were shown on modulus of elasticity of UHPC.…”
Section: Resultsmentioning
confidence: 82%
“…As it is clearly visible in Figure 3a, increasing the superplasaticizer decreased the modulus of elasticity that is because of increasing the workability and porosity of concrete [10]. Also, increasing the amount of cement increased the modulus of elasticity of UHPC which is due to increasing of hydration and packing density [11,12]. In Figure 3b, effect of w/c cement were shown on modulus of elasticity of UHPC.…”
Section: Resultsmentioning
confidence: 82%
“…By evaluating the case of Fochen West Bridge in China, Zhu et al [10] believed that UHPC-OSD system presents adequate anti-fatigue capability, and that much smaller maximal stress can be expected in all details compared with the previous one. Also, Xu et al [11] concluded that the orthotropic steel deck bridge after the reinforcement of UHPC layer can last for more than 100 years. Hesham et al [12] suggested that the crack formation life rises 236% while applying the UHPC overlayer.…”
Section: Application Of Uhpc In the Osd Fatigue Reinforcementmentioning
confidence: 99%